Solubilization and characterization of extracellular proteins from anammox granular sludge. (1st November 2019) - Boleij, Marissa; Seviour, Thomas; Wong, Lan Li; van Loosdrecht, Mark C.M.; Lin, Yuemei
Abstract: Elucidating the extracellular polymeric substances (EPS) of anammox granular sludge is important for stable nitrogen removal processes in wastewater treatment. However, due to a lack of standardized methods for extraction and characterization, the composition of anammox granule EPS remains mostly unknown. In this study, alkaline (NaOH) and ionic liquid (IL) extractions were compared in terms of the proteins they extracted from different " Candidatus Brocadia" cultures. We aimed to identify structural proteins and evaluated to which extend these extraction methods bias the outcome of EPS characterization. Extraction was focussed on solubilization of the EPS matrix, and the NaOH and IL extraction recovered on average 20% and 26% of the VSS, respectively. Using two extraction methods targeting different intermolecular interactions increased the possibility of identifying structural extracellular proteins. Of the extracted proteins, ∼40% were common between the extraction methods. The high number of common abundant proteins between the extraction methods, illustrated how extraction biases can be reduced when solubility of the granular sludge is enhanced. Physicochemical analyses of the granules indicated that extracellular structural matrix proteins likely have β-sheet dominated secondary structures. These β-sheet structures were measured in EPS extracted with both methods. The high number of uncharacterized proteins and possible moonlighting proteins confounded identifying structural (i.e. β-sheet dominant) proteins. Nonetheless, new candidates for structural matrix proteins are described. Further current bottlenecks in assigning specific proteins to key extracellular functions in anammox granular sludge are discussed. Graphical abstract: Image 1 Highlights: Alkaline and ionic liquid extractions allow efficient extraction of EPS of anammox granules. Extraction biases were minimized when solubilization was enhanced. Extracellular protein rich in β-sheets might fulfil structural role in granules.